Advances in ceramic armor IX : a collection of papers presented at the 37th International Conference on Advanced Ceramics and Composites, January 27-February 1, 2013, Daytona Beach, Florida - International Conference on Advanced Ceramics and Composites 2013 : Daytona Beach, Florida); LaSalvia, Jerry C.; Kirihara, Soshu; Widjaja, Sujanto (Hoboken, New Jersey : Wiley, 2014)
Ceramic Engineering and Science Proceedings Volume 34, Issue 5 - Advances in Ceramic Armor IX A collection of 14 papers from The American Ceramic Society's 37th International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 27-February 1, 2013. This issue includes papers presented in the Armor Ceramics Symposium on topics such as Manufacturing; High-Rate Real-Time Characterization; Microstructural Design; Nondestructive Characterization; and Phenomenology and Mechanics of Ceramics Subjected to Ballistic Impact.<h.
Al/Al2O3 MMCs and Macrocomposites for Armor ApplicationsMechanical Response Anisotropy in Hot-Pressed Silicon Carbide; Comparison of Armor Ceramics Made by Spark Plasma Sintering (SPS) and Pressureless Sintering; Pressureless Sintering of SiC-B4C Composites; Development of Transparent Polycrystalline Beta-Silicon Carbide Ceramic using Field Assisted Sintering Technology; Densification of Synthesized Boron Carbide Powders using SPS; Consolidation of Aluminum Magnesium Boride (AIMgB14) by Pulsed Electric Current Sintering (PECS) Technique.
"American Ceramic Society."
Includes bibliographical references.
Ultrasonic Nondestructive Characterization of Transparent Spinel MicrostructureAuthor Index.
Online resource; title from PDF title page (Wiley, viewed December 6, 2013).
Keywords: Ceramic materials -- Congresses; Electric insulators and insulation -- Ceramic materials -- Congresses; Insulation (Heat) -- Congresses; Armor-plate -- Materials -- Congresses; Ceramic materials -- Congresses; Composite materials -- Congresses; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Ceramic materials; Electric insulators and insulation -- Ceramic materials; Insulation (Heat); Electronic books; Conference papers and proceedings